Role of Grasses in Soil Conservation - Rege, N.D. (Journal of Soil and Water Conservation, 2022)
The day man started extensive as well as intensive cultivation, the probletn of soil erosion also made its appearance. As soon the land covered with natural vegetation was deprived of its protective cover to bring it under cultivation, it was left to the mercy of the destructive elenwnts of nature. Due to the itnpact of rain and wind the exposed soil gets bodily pushed and the land gefs more an(l more eroded. At present most o! the world's agriculture is being carried out on such eroded lands, the result of faulty agricultural practices. I here has been con- siderable loss of fertility due to progressive erosion finally resulting in the fall of productive capacity of the land. Basu, Sirur and Puranikl during their study on soil erosion survey of about 80,000 acres in the semi-arid region of the Bombay State have found 17-20 per cent of the area in the Deccan and Karnatak has been slightly eroded while, 69 and 73 per cent of the Ian(l respectively has been found to have been erode more or less severely. Consequently there has been a great amount of deterioration in the fertility status of the soil in these regions. Further the removal of protective vegetation in favour of continuous cropping results in the pulverized state of the soil and destruction of its grannular structure. It has been proved that, for better production, the soilmust have grannular structure. In this connection  it is observed that under natural or artificially laid-out grassland this type of can be developed. In Europe grass has been considered as an indispensable item the agricultural programme of the country. This system of alternate husbandry ' consists mainly of rotation of arable crops with leys of varying duration. In New Zealand and Australia, Inany areas adopt a similar type of farnling in order to avoid the destruction of the land. It is true that man must cultivate the soil to meet his daily needs of food and clothing. However, it must be borne in mind that the land which supports him and the nation should not be allowed to bc deteriorated by adopting faulty practices of cultivation. Therefore, a method or methods are to be found out to control the soil erosion and improve the fertility status of the soil. These methods consist of adopting suitable agronomical and agrostological practices sometimes combining them with mechanical measures. One of them is to use close growing crops such as grass and/ or legume which not only control soil erosion but improxw• the soil fertility. By growing grasses and legumes alternately  with cereals one can meet his needs of food as well as control the loss of soil.